Role of Human Leukocyte Antigen Allele Sharing in Human Papillomavirus Infection Transmission Among Heterosexual Couples: Findings From the HITCH Cohort Study . (1st April 2022) - Louvanto, Karolina; Baral, Prativa; Burchell, Ann; Ramanakumar, Agnihotram; El-Zein, Mariam; Tellier, Pierre Paul; Coutlée, Francois; Roger, Michel; Franco, Eduardo L
Abstract: Background: Human leukocyte antigen (HLA) polymorphism influences innate and adaptive immune responses. Among heterosexual couples in the HPV Infection and Transmission Among Couples Through Heterosexual Activity (HITCH) cohort study, we examined whether allele sharing in a couple predicted the partners' infections with the same human papillomavirus (HPV) type. Methods: We tested genital samples from 271 couples for 36 HPV genotypes by polymerase chain reaction. We used direct DNA sequencing to type HLA-B07, -DRB1, -DQB1 and -G. Generalized estimating equations were used to examine the associations between the extent of allele sharing and HPV type concordance in which at least 1 of the partners was HPV positive. Results: We identified 106 different HLA alleles. The most common HLA alleles among couples were G*01:01:01 (95.6%), G*01:01:02 (60.1%), DQB1*03:01 (57.2%), and DRB1*07:01 (46.9%). Allele sharing was as follows: 19.6% shared none, 43.2% shared 1 only, 25.1% shared 2, and 12.5% shared 3–5. Irrespective of HLA class, grouped or in combination, the extent of allele sharing was not a significant predictor of type-specific HPV concordance in a couple (odds ratio,  1.1 [95% confidence interval, .5–2.1], for 3–5 vs none). Conclusions: We found no evidence that the extent of HLA allele concordance influences the likelihood of HPV transmission in newly formed heterosexual couples. Abstract : Among heterosexual couples, we examined whether human leukocyte antigen (HLA) allele sharing in a couple predicted the partners' infections with the same human papillomavirus (HPV) type. Our evaluations, however, could not provide evidence that the extent of HLA allele concordance influences the likelihood of HPV transmission.